Measuring international price and cost competitiveness - Turner, Philip; Dack, Jozef van't; Bank for International Settlements (Basle : Bank for International Settlements, Monetary and Economic Dept., 1993)
This paper focuses on relative prices and costs. The link between this narrow concept and economic performance more generally is not unambiguous. The ambiguity arises from the fact that its international relative price or cost position can be both cause and result of a country's economic performance
"November 1993."
Includes bibliographical references (p. 141-149).
osc 31/01/2019
Loans
Keywords: Foreign exchange rates; Prices; Cost; Competition, International